Expandiendo el aula a través del microblogging - Alberto Corpas Martos; Raúl Rubio Millares (Universidad de Cádiz, 2017)
Mediated learning through Learning and Knowledge Technologies makes formal learning grow. In this experience, we propose the use of the Tumblr microblogging site, as a way to expand spatiotemporally the classroom. The methodology tries to offer a personalized attention to the characteristics of each student, enhancing the teacher's support role and the advantages of the formative evaluation. It is intended to leave more room for creativity, the possibility of becoming creators of digital artefacts and enrich the acquisition and dissemination of information. All this implies a functional and significant learning, in real contexts, not only of the contents related to the area, but also of responsible and enriching uses of digital media.